2017
DOI: 10.1016/j.nmni.2017.05.011
|View full text |Cite|
|
Sign up to set email alerts
|

Description of ‘Arabia massiliensis’ gen. nov., sp. nov., ‘Gordonibacter massiliensis’ sp. nov., and ‘Bacilliculturomica massiliensis’ gen. nov., sp. nov., isolated from a faecal specimen of a 50-year-old Saudi Bedouin woman

Abstract: We report here the main characteristics of ‘Arabia massiliensis’ strain Marseille-P3078T gen. nov., sp. nov., ‘Gordonibacter massiliensis’ Marseille-P2775T sp. nov. and ‘Bacilliculturomica massiliensis’ strain Marseille-P3303 gen. nov., sp. nov. The culturomics approach combined with taxonogenomics was used to characterize these strains, which were all isolated from a faecal specimen of a 50-year-old Saudi Bedouin woman.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Both A. massiliensis (recently identi ed in stool material) 40 and F. nucleatum (the by far most CRCassociated bacterium in previous studies) were highly detected among the RNA sequences of the mucosa and the tumors, respectively. Compared to DNA analysis, A. massiliensis did not surpass the established cut-off, and F. nucleatum did reach it, but its relative abundance presence was low and not different between tumor and healthy mucosa specimens.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Both A. massiliensis (recently identi ed in stool material) 40 and F. nucleatum (the by far most CRCassociated bacterium in previous studies) were highly detected among the RNA sequences of the mucosa and the tumors, respectively. Compared to DNA analysis, A. massiliensis did not surpass the established cut-off, and F. nucleatum did reach it, but its relative abundance presence was low and not different between tumor and healthy mucosa specimens.…”
Section: Discussionmentioning
confidence: 74%
“…This study demonstrated how deep sequencing of both DNA and RNA enables a wider perspective of microbiome pro les: individual microbial features can vary depending on whether the metagenome or metatranscriptome is analysed. The role of the recently identi ed A. massiliensis 40 needs to be further investigated to elucidate its implications in human health. While F. nucleatum is already known to be a potential colorectal cancer biomarker for screening, diagnosis, and prognosis prediction for patient outcomes 11-14 , the association mainly with transcription of F. nucleatum may provide further insights on the role of this microorganism in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on skin have detected several hundreds of human papillomavirus types when analyzing DNA sequences, but most of these viruses were not actively transcribed (apparently representing deposition). 37 Both A. massiliensis (recently identified in stool material) 38 and F. nucleatum (the by far most CRC-associated bacterium in previous studies) were highly detected among the RNA sequences of the mucosa and the tumors, respectively. Compared to DNA analysis, A. massiliensis did not surpass the established cut-off, and F. nucleatum did reach it, but its relative abundance presence was low and not different between tumor and healthy mucosa specimens.…”
Section: Discussionmentioning
confidence: 87%
“…The role of the recently identified A. massiliensis 38 and P. necessarius needs to be further investigated to elucidate their implication in human health. The present study comprised strict cut‐offs to focus the analysis only on abundant species (species present only in small amounts may conceivably represent contamination and were therefore not studied); however, validation of these “putative” findings would be desirable and findings may need to be considered carefully.…”
Section: Discussionmentioning
confidence: 99%